Integrating Population Education in Sekolah Siaga Kependudukan (SSK) in Building a Planned Generation - Septiani, Endah; Setyowati, Dewi Liesnoor; Atmaja, Hamdan Tri (JESS (Journal of Educational Social Studies), 2022)
To solve increasing population in Indonesia, population education can be implemented in school. The purpose of this study was to analyze the integration of population education in SSK as an effort to realize a planned generation. A phenomenological design with an interview, observation, and documentation was employed in this research. The study's results showed that the integration process of population education in secondary schools occurred through teaching and learning and extracurricular activities, school programs, and pojok kependudukan (population corner). The integration of population education in SSK is inseparable from adaptation, goal attainment, integration, and latency, creating a substantial value and resilience system. The novelty of the research lies in the analysis of Talcott Parsons' structural-functional theory to integrate SSK for the Planned Generation with an adaptation process, where students learn about various population issues. The integration of multiple parties raises students' self-awareness to reach marriage-age maturity, avoiding premarital sex, and sustainably maintain their reproductive health. However, the iintegration requires a more effective delivery medium for the current generation. Therefore, it is necessary to use technology-based population education media that students can utilize. Meanwhile, for science, population-based technology can also be an innovation in streamlining the integration process of population education.